Diagnosis of non-expandable lung using thoracic ultrasound. (2022) - Khatim, Ibrahim; Albaba, Isam; Hu, Kurt; Huggins, Terrill; Chopra, Amit
Abstract: Non-expandable lung (NEL) commonly occurs secondary to chronic pleural processes, including pleural effusions, endobronchial obstruction, atelectasis, or chronic pleural inflammatory processes. Patients with NEL frequently undergo unnecessary procedures (e.g., thoracentesis), resulting in pneumothorax and discomfort (usually chest pain). Identifying a chronic process and likely development of NEL may prevent this. Diagnostic modalities currently used in practice include pleural manometry and ultrasonography. This case report demonstrates that blunting of transmitted cardiac impulse on M-Mode of ultrasonography predicts the presence of NEL.